Respiratory health symptoms and lung function among roadside Hawkers in Serdang and its association with traffic-related exposures - Amaran, Nur Afiqah; Zainal Abidin, Emilia; Rasdi, Irniza (Tehran University of Medical Sciences, 2016)
Background: The main objective of this study was to determine the respiratory health symptoms and lung function among roadside hawkers in Serdang, Malaysia and its association with traffic-related exposures. Methods: This cross-sectional comparative study was conducted among 60 roadside hawkers while 60 restaurant workers were included as the comparative group in 2015. A questionnaire was used to collect background information and symptoms of respiratory health. All participants performed lung function tests. Personal exposure to traffic-related fine particulate matter (PM2.5) and carbon dioxide (CO) were performed among a representative group of workers. All statistical analysis was performed using SPSS version 22. Results: The mean (standard deviation) PM2.5 exposure among the roadside hawkers was 31.05 (1.62) μg/m3 while the exposure among the comparative group was 19.41 (1.51) μg/m3 (P<0.05). The mean exposure level of CO among the roadside hawkers was 2.42 (0.29) ppm compared to 1.51 (0.14) ppm among comparative group. FEV1 (litres) (z=-1.96, P=0.04) of the exposed group was significantly lower than the comparative group. Respiratory symptoms such as wheezing, chest tightness, coughing and phlegm were significantly higher among exposed group (P<0.05). There were significant associations between the reporting of wheezing with PM2.5 (Odds Ratio, OR=10.39, 95% Confidence Interval, CI=2.67-40.41), working duration (OR=13.36, 95%CI=3.13- 57.03) and current smoking status (OR=3.34, 95%CI=1.04-10.67). Conclusion: Roadside hawkers are exposed to high traffic-related pollutants, had reduced lung function, and are at risk for increased respiratory health symptoms. The study suggested the importance of preventive management for this specific group of workers.